Ensuring Institutional Development of the Real Sector of the Economy of the Republic of Uzbekistan (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article discusses the state of the real sector of the economy of the Republic of Uzbekistan, its macroeconomic indicators, assesses the specifics of the real sector of the economy of Uzbekistan, suggests tools to increase demand for products of enterprises in the real sector of the economy.